MENTAL HEALTH AND THE JUVENILE JUSTICE SYSTEM: A RIGHTS-BASED JUDICIAL APPROACH IN INDIA - Hussain, Mujataba Noorul; Mali, Mahaveer Prasad; Rehman, Sadaqat (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Indian judiciary has progressively expanded the interpretation of juvenile rights to include mental health and psychosocial well-being as integral to the right to life and dignity under Article 21 of the Constitution. Judicial pronouncements have emphasized that children in conflict with the law and those in need of care and protection must be treated through a rehabilitative, not punitive, lens. Courts have recognized the deep psychological impact of institutionalization, neglect, trauma, and stigma on juveniles and have directed authorities to ensure child-friendly procedures, regular mental health assessments, and access to counselling and psychological support in Child Care Institutions. Further, the judiciary has encouraged the integration of trauma-informed practices into all stages of juvenile justice administration, from apprehension and inquiry to rehabilitation and aftercare. The use of individualized care plans, trained mental health professionals, and the establishment of child-friendly spaces have been judicially endorsed to foster a safe and enabling environment. These developments reflect a rights-based approach grounded in international child protection standards. To strengthen these gains, it is imperative to ensure interlinkages between juvenile justice laws and mental healthcare frameworks, along with sustained capacity-building of all stakeholders involved.